The teacher from the Black Lagoon and other stories - Thaler, Mike, 1936-; Lee, Jared D. (New York : Scholastic, 2006)
Compilation of four Black Lagoon stories in which young Hubie must face the monstrous adults who run his school.
The teacher from the Black Lagoon -- The gym teacher from the Black Lagoon -- The principal from the Black Lagoon -- The librarian from the Black Lagoon.
2.6
K-3
Keywords: Monsters -- Juvenile fiction; Schools -- Juvenile fiction; Fear -- Juvenile fiction; Monsters -- Fiction; Schools -- Fiction; Fear -- Fiction; Monsters -- Fiction; School stories; Teachers -- Fiction; School principals -- Fiction; Librarians -- Fiction; Humorous stories